A speedy route to sterically encumbered, benzene-fused derivatives of privileged, naturally occurring hexahydropyrrolo[1,2-b]isoquinoline - Bakulina, Olga; Ivanov, Alexander; Suslonov, Vitalii; Dar’in, Dmitry; Krasavin, Mikhail (Beilstein Journal of Organic Chemistry, 2017)
A series of 15 benzene-fused hexahydropyrrolo[1,2-b]isoquinolonic acids with substantial degree of steric encumbrance has been prepared via a novel variant of the Castagnoli–Cushman reaction of homophthalic anhydride (HPA) and various indolenines. The employment of a special kind of a cyclic imine component reaction allowed, for the first time, isolating a Mannich-type adduct between HPA and an imine component which has been postulated but never obtained in similar reactions.
Keywords: Castagnoli–Cushman reaction; diastereoselectivity; homophthalic anhydride; indolenines; lactam synthesis; multicomponent reactions

(untitled) - Krasavin, M.; Dar’in, D. (Tetrahedron Lett., 2016)

(untitled) - Castagnoli, N., Jr (J. Org. Chem., 1969)

(untitled) - Cushman, M.; Castagnoli, N., Jr (J. Org. Chem., 1973)

(untitled) - Adamovskyi, M. I.; Ryabukhin, S. V.; Sibgatulin, D. A.; Rusanov, E.; Grygorenko, O. O. (Org. Lett., 2017)

(untitled) - Bakulina, O.; Dar’in, D.; Krasavin, M. (Synlett, 2017)

(untitled) - Wang, L.; Liu, J.; Tian, H.; Qian, C.; Sun, J. (Adv. Synth. Catal., 2005)

(untitled) - Mohammadi, M. H.; Mohammadi, A. A. (Synth. Commun., 2011)

(untitled) - Karimi, A. R.; Momeni, H. R.; Pashazadeh, R. (Tetrahedron Lett., 2012)

(untitled) - Humphries, P. S.; Benbow, J. W.; Bonin, P. D.; Boyer, D.; Doran, S. D.; Frisbie, R. K.; Piotrowski, D. W.; Balan, G.; Bechle, B. M.; Conn, E. L.; Dirico, K. J.; Oliver, R. M.; et al. (Bioorg. Med. Chem. Lett., 2009)

(untitled) - Rothweiler, U.; Czarna, A.; Krajewski, M.; Ciombor, J.; Kalinski, C.; Khazak, V.; Ross, G.; Skobeleva, N.; Weber, L.; Holak, T. A. (ChemMedChem, 2008)

(untitled) - Dar’in, D.; Bakulina, O.; Chizhova, M.; Krasavin, M. (Org. Lett., 2015)

PCT Int. Appl. - Liu, H.; Li, G.; Wang, J.; Liu, J. (Corydaline derivatives useful for reducing lipid levels, 2009)
Chem. Abstr. 2010, 153, 145700.

(untitled) - Georgieva, A.; Stanoeva, E.; Spassov, S.; Macicek, J.; Angelova, O.; Haimova, M.; De Kimpe, N. (Tetrahedron, 1991)

(untitled) - Stanoeva, E.; Georgieva, A.; Avramova, S.; Burdzhiev, N.; Lázár, L. (J. Heterocycl. Chem., 2015)

(untitled) - Smith, F. T.; DeRuiter, J.; Carter, D. A. (J. Heterocycl. Chem., 1989)

(untitled) - Smith, F. T.; Atigadda, R. V. (J. Heterocycl. Chem., 1991)

(untitled) - Venkatram, A.; Colley, T.; DeRuiter, J.; Smith, F. (J. Heterocycl. Chem., 2005)

(untitled) - Mulchandani, N. B.; Venkatachalam, S. R. (Phytochemistry, 1976)

(untitled) - Padwa, A.; Brodney, M. A.; Lynch, S. M. (J. Org. Chem., 2001)

(untitled) - Sun, Z.; Zhou, M.; Li, X.; Meng, X.; Peng, F.; Zhang, H.; Shao, Z. (Chem. – Eur. J., 2014)

(untitled) - Schramm, A.; Saxena, P.; Chlebek, J.; Cahlikova, L.; Baburin, I.; Hering, S.; Hamburger, M. (Planta Med., 2014)

(untitled) - Wang, C.; Wang, Q.; Li, X.; Jin, X.; Xu, P.; Xu, N.; Xu, A.; Xu, Y.; Zheng, S.; Zheng, J.; Liu, C.; Huang, P. (Biochem. Biophys. Res. Commun., 2017)

(untitled) - Guo, Y.; Wang, Y.; Cao, L.; Wang, P.; Qing, J.; Zheng, Q.; Shang, L.; Yin, Z.; Sun, Y. (Antimicrob. Agents Chemother., 2016)

(untitled) - Chen, C.-Y.; Zhu, G.-Y.; Wang, J.-R.; Jiang, Z.-H. (RSC Adv., 2016)

(untitled) - Evans, B. E.; Rittle, K. E.; Bock, M. G.; DiPardo, R. M.; Freidinger, R. M.; Whitter, W. L.; Lundell, G. F.; Veber, D. F.; Anderson, P. S.; Chang, R. S. L.; Lotti, V. J.; Cerino, D. J.; et al. (J. Med. Chem., 1988)

(untitled) - Golubev, P.; Bakulina, O.; Dar'in, D.; Krasavin, M. (Eur. J. Org. Chem., 2016)

(untitled) - Estévez, V.; Kloeters, L.; Kwietniewska, N.; Vicente-García, E.; Ruijter, E.; Orru, R. V. A. (Synlett, 2017)

(untitled) - Golubev, P.; Krasavin, M. (Eur. J. Org. Chem., 2017)

(untitled) - Lovering, F.; Bikker, J.; Humblet, C. (J. Med. Chem., 2009)

(untitled) - Ling, T.; Rivas, F. (Tetrahedron, 2016)

(untitled) - Luo, W.-K.; Shi, X.; Zhou, W.; Yang, L. (Org. Lett., 2016)

(untitled) - Sarnpitak, P.; Krasavin, M. (Tetrahedron Lett., 2014)

(untitled) - Georgieva, A.; Stanoeva, E.; Karafilova, K.; Spassov, S.; Angelova, O.; Haimova, M.; De Kimpe, N.; Boelens, M. (Tetrahedron, 1994)

(untitled) - Lepikhina, A.; Bakulina, O.; Dar'in, D.; Krasavin, M. (RSC Adv., 2016)

(untitled) - Hong, J.; Wang, Z.; Levin, A.; Emge, T. J.; Floyd, D. M.; Knapp, S. (Tetrahedron Lett., 2015)

(untitled) - Ji, C.; Ma, L.; Yin, M.; Yang, W.; Pan, K. (Chem. – Asian J., 2016)

(untitled) - Szalóki, G.; Sanguinet, L. (J. Org. Chem., 2015)

(untitled) - Balmond, E. I.; Tautgeg, B. K.; Faulkner, A. L.; Or, V. W.; Hodur, B. M.; Shaw, J. T.; Louie, A. Y. (J. Org. Chem., 2016)

(untitled) - Schultz-Senft, M.; Gates, P. J.; Soennichsen, F. J.; Stanbitz, A. (Dyes Pigm., 2017)

(untitled) - Prostoba, Y.; Coelho, P. J.; Pina, J.; Seixas de Melo, J. (J. Photochem. Photobiol., A: Chem., 2010)